Alienation Among Older Persons: A Comparative Analysis. Issue 5 (19th October 2020) - Joseph, Sheeba; Dash, Bishnu Mohan
Abstract : The present research tried to find out difference in the feeling of alienation among the male and female older people. The data was collected from older people (N = 255) residing in the Urban areas of Bhopal, India. The study tried to analyse the significance difference in the feeling of alienation in male and female elderly. It was observed that females (60.33 ± 9.51) experiences more alienation than males (57.61 ± 8.85). Leven's test for equality of variance which shows [F(1, 253)=.734, Sig. =.392] and t = 2.357, p=.01, (p<.05). The lower educational status of the older females makes it difficult for them to move easily along with the changing world. Also when compared to the older males, the lower degree of social contacts and activities of the older females may increase the isolation. At a time when help, care, support and presence of children, family members, friends and neighbours are most desired, the greater feelings of alienation are quite natural.